Effect of Ti/Al Ratio on the Elemental Partitioning in the Face-Centered Cubic-Based γ-γ′ Dual-Phase High Entropy Alloy Studied by Atom Probe Tomography - Han, Bin; He, Feng; Xia, Linfei; Wang, Zhijun; Kai, Ji Jung (Frontiers in Materials, 2022)
The effect of Ti/Al ratio on the elemental partitioning in the Ni2CoFeCrTixAly high entropy alloy was studied by atom probe tomography (APT). The APT results indicate that the γ' nanoparticles have a composition of (NiCoFeCr)3TiAl which is independent of Ti/Al ratio. The effect of Ti/Al ratio on the partitioning behaviors of Fe and Cr are significantly different from that of Co. The decreasing of Ti/Al ratio significantly enhanced the incorporation of Fe and Cr into the γ' nanoparticles. However, the concentration of Co in the γ' nanoparticles declined with the decrease of Ti/Al ratio.